Global Best Practices in Transit Facilitation and Supply Chain Management: Exploring Opportunities for Nepal - Prakash Prasad Pokharel, (Journal of Development and Administrative Studies, 2024)
Transit facilitation and supply chain management are crucial for improving trade competitiveness, especially for landlocked countries like Nepal, which faces unique challenges due to its dependence on neighboring nations, particularly India, for access to global trade routes. This article explores global best practices in transit facilitation and supply chain management, highlighting how countries with similar geographical constraints, such as Switzerland and Austria, have effectively addressed logistical challenges through integrated infrastructure, digitalization, and regional cooperation. It examines how these strategies can be adapted to Nepal’s context to optimize its transit systems, reduce costs, and enhance its trade competitiveness. Key strategies include streamlining customs procedures, adopting digital integration like blockchain and Electronic Data Interchange (EDI), and investing in efficient infrastructure, such as multimodal transport systems and dry ports. The article also underscores the importance of regional cooperation, exemplified by frameworks like ASEAN, which can offer Nepal opportunities to harmonize policies and reduce trade barriers. Furthermore, Nepal’s transit challenges—ranging from its dependency on India, infrastructure gaps, bureaucratic delays, and limited digitalization—are discussed, with actionable recommendations for overcoming these obstacles. Opportunities for Nepal include leveraging the India-Nepal Transit Treaty, enhancing digital platforms for transparency, improving infrastructure, and strengthening regional cooperation. By aligning with global best practices and strategically addressing its challenges, Nepal can improve its logistics and transit systems, foster economic growth, and enhance its position in regional and global trade networks. This study provides a comprehensive roadmap for Nepal to build resilience and competitiveness in the evolving global trade landscape.